Adherence to Long-Term Interferon Beta-1b Injection Therapy in Patients with Multiple Sclerosis Using an Electronic Diary. Issue 5 (May 2016) - Zettl, Uwe; Bauer-Steinhusen, Ulrike; Glaser, Thomas; Czekalla, Jörg; Hechenbichler, Klaus; Limmroth, Volker; Hecker, Michael
Abstract Introduction Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system requiring long-term treatment, which is often hampered by non-adherence to self-applicable therapies, provoking continued disease activity and health care system burdens. This study assessed the influence of a personal digital assistant (PDA) with diary function (n  = 339 patients) on persistence and adherence to an interferon beta treatment regimen in comparison to a paper patient diary (n  = 330 patients). Methods Patients who recently started with subcutaneous injections of interferon beta-1b were recruited in this prospective, non-interventional, national cohort study for an observational period of 2 years after successful completion of the initial dose escalation. Results Therapy persistence as assessed by the drop-out rate within 104 weeks was about 50% in both study cohorts. In male patients, the drop-out rate was 10% lower when using a PDA compared to the non-PDA group. Use of a PDA with an injection reminder function increased adherence to the injection schedule (every other day) by a mean of 24.5 injections over 24 months in comparison to use of a PDA without injection reminder function. Conclusion Persistence in this study was in the published range of observational MS studies. Furthermore, in male patients continuation of therapy might be positively influenced by use of a PDA, and both female and male patients might benefit from an integrated reminder function. In conclusion, electronic diaries reminding patients of upcoming injections can promote an improved adherence to MS therapy. Trial registration ClinicalTrials.gov identifier: NCT00902135. Funding Bayer Vital GmbH.